2007
DOI: 10.1152/ajpheart.00382.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphic ventricular tachycardia and abnormal Ca2+handling in very-long-chain acyl-CoA dehydrogenase null mice

Abstract: Patients with mutations in the mitochondrial very-long-chain acyl-CoA dehydrogenase (VLCAD) gene are at risk for cardiomyopathy, myocardial dysfunction, ventricular tachycardia (VT), and sudden cardiac death. The mechanism is not known. Here we report a novel mechanism of VT in mice lacking VLCAD (VLCAD−/−). These mice exhibited polymorphic VT and increased incidence of VT after isoproterenol infusion. Polymorphic VT was induced in 10 out of 12 VLCAD−/− mice (83%) when isoproterenol was used. One out of 10 VLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Although the exact pathogenesis of diabetic cardiomyopathy is still poorly understood, alterations in lipid metabolism have been suggested to be an important mediator [43]. In this context, patients and genetically altered mice with defects in fat metabolism, i.e., infants with very long chain acyl-CoA dehydrogenase (VLCAD) deficiency [39] and VLCAD null mice [47] have been characterized by prolonged QT intervals, ventricular tachycardia or fatal arrhythmias similar to the etomoxir-administered UCP3 −/− mice. In VLCAD null mice, abnormal Ca 2+ handling is suggested as a possible molecular mechanism of arrhythmias [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact pathogenesis of diabetic cardiomyopathy is still poorly understood, alterations in lipid metabolism have been suggested to be an important mediator [43]. In this context, patients and genetically altered mice with defects in fat metabolism, i.e., infants with very long chain acyl-CoA dehydrogenase (VLCAD) deficiency [39] and VLCAD null mice [47] have been characterized by prolonged QT intervals, ventricular tachycardia or fatal arrhythmias similar to the etomoxir-administered UCP3 −/− mice. In VLCAD null mice, abnormal Ca 2+ handling is suggested as a possible molecular mechanism of arrhythmias [47].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, patients and genetically altered mice with defects in fat metabolism, i.e., infants with very long chain acyl-CoA dehydrogenase (VLCAD) deficiency [39] and VLCAD null mice [47] have been characterized by prolonged QT intervals, ventricular tachycardia or fatal arrhythmias similar to the etomoxir-administered UCP3 −/− mice. In VLCAD null mice, abnormal Ca 2+ handling is suggested as a possible molecular mechanism of arrhythmias [47]. Given recent hypotheses on a role for UCP3 in cellular Ca 2+ handling [6, 8], it is tempting to speculate that modulation of repolarization in the UCP3 −/− mice results from an attempt of cardiomyocytes to maintain Ca 2+ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the aforementioned fatalities is that upon adrenergic stimulation VLCAD-/-deficient mice might exhibit polymorphic ventricular tachycardia and arrhythmias (Exil et al 2003). Even though the mechanism is not well understood, a recent study (Werdich et al 2007) suggested that impaired intracellular Ca 2? handling could be the possible molecular mechanism of arrhythmias in VLCADdeficient mice and perhaps in VLCAD-deficient humans.…”
Section: Discussionmentioning
confidence: 99%
“…The pentobarbital that was used in this study to sedate the mice was found to significantly decrease cardiac hemodynamics and performance in mice due to inhibition of sympathetic activity and myocardial contractility (Yang et al 1999). In addition, the anesthesia effects might have masked any functional differences since it suppressed the sympathetic nervous system activity which in turn was found (Werdich et al 2007) to cause arrhythmias in VLCAD deficiency after stimulation.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The L-type Ca current characteristics were not different compared with controls but the SR function was altered with an increase in the SR Ca load (up to 48%) and Ca transients amplitude, similar to the mouse models of Casq2 overexpression. Protein assays of the very long-chain acyl-CoA dehydrogenase mutant mice show an upregulation of RyR2, Casq2, and phospholamban (103).…”
Section: Potential Role Of Casq2 In Acquired Arrhythmiasmentioning
confidence: 99%